Harry Potter and the prisoner of Azkaban - Rowling, J. K. (Bloomsbury, 1999)
During his third year at Hogwarts School for Witchcraft and Wizardry, Harry Potter must confront the devious and dangerous wizard responsible for his parents' deaths.